The Igil and Exeter Book Riddle 15 - Cavell, M (Oxford University Press, 2017)
Riddle 15 is one of the longest and most elaborate animal-riddles in the tenth-century Exeter Book of Old English poetry. The debate over which animal appears in this compelling tale of a family’s flight and the mother’s final stand against their canine attacker has not yet been put to rest. In a recent, comprehensive analysis of this riddle, Dieter Bitterli comes to the conclusion that the creature in question is a porcupine. However, given the fox’s rivalry with dogs and wolves, this animal (or, specifically, a vixen ) also receives wide support. I am of the opinion that both solutions have merit and either one could be correct. In suggesting that, rather than ‘porcupine’, adherents of Bitterli’s interpretation should solve the riddle as igil, this note both supports and nuances his conclusions and reminds solvers that a solution in the language of the riddle is always preferable to one that draws on modern linguistic forms and categorisations.